Tradisi Pendidikan Pesantren di Pesantren At-Taubah Lembaga Pemasyarakatan Klas II B Cianjur dalam Membina Akhlak Santri Warga Binaan - Siti Lutfi Latifah; Siti Aminah; Muhammad Afri Hamzah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
Islamic Boarding School is a boarding school that was established in a Penitentiary in Cianjur to be precise in the Cianjur Class II B Correctional Institution, not just as a form of spiritual guidance that must be given by each lap to its fostered citizens but is actually a boarding school that stands within the Correctional Institution. One of which is indicated by the statistical number of Islamic boarding schools provided by the Ministry of Religion, The purpose of writing this paper is to find out the educational traditions of the Islamic boarding school at the At-Taubah Islamic Boarding School in fostering the morals of the assisted students in the Cianjur Class II B Penitentiary. The approach used in writing this paper is a qualitative approach with the case study method, the results of this paper state that the pesantren tradition implemented at the At-Taubah Islamic Boarding School is like the pesantren tradition in general by fulfilling the five elements of the Islamic boarding school, namely the presence of Santri, namely all Fostered Residents in Cianjur Class II B Prison which is Muslim, Kyai as the Leader of the Islamic Boarding School and 31 Asatdi who are members of the MUI organization, teaching the yellow book which is carried out using the bandongan method in the executive class and nadzom in the BTQ class, the cottage is the cell and the mosque. However, the focus of the pesantren's activities is to raise the awareness of the assisted residents so that they do not repeat the mistakes they have made. The pesantren tradition which is carried out as a whole has succeeded in forming the akhlakul karimah of the students of the assisted residents as indicated by the presence of students who have finished their coaching period, some of whom have become asatid or Koran teachers, muezzins at the Cianjur Great Mosque, school principals and others. Keywoards: Traditions, Islamic Boarding Schools, Morals, Warga Binaan